2004
DOI: 10.1002/jpln.200321284
|View full text |Cite
|
Sign up to set email alerts
|

Effect of post‐methanation effluent on soil physical properties under a soybean‐wheat system in a Vertisol

Abstract: SummaryPost-methanation effluent (PME) generated through biomethanation of distillery effluent, a foul-smelling, dark colored by-product of distillery industries, is applied to arable land in some areas near the vicinity of the distillery industries as an amendment. The PME contains considerable amount of organic matter and salt besides its high plant-nutrient content. The present investigation was conducted for three years during 1999±2002 on soybean-wheat cropping sequence to evaluate the effect of graded le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…Similar findings were also reported by [15], in green leafy vegetables. Delayed growth reported during the primary stage of the sugarcane sapling was agreed in the previous studies [16]. [17] reported that higher concentration of effluent causes delayed shoot growth, seedling growth and chlorophyll content in sunflower (Helianthus annuus) and it could be safely used for irrigation purpose at low concentration.…”
Section: Sugarcane Sapling Growthsupporting
confidence: 83%
“…Similar findings were also reported by [15], in green leafy vegetables. Delayed growth reported during the primary stage of the sugarcane sapling was agreed in the previous studies [16]. [17] reported that higher concentration of effluent causes delayed shoot growth, seedling growth and chlorophyll content in sunflower (Helianthus annuus) and it could be safely used for irrigation purpose at low concentration.…”
Section: Sugarcane Sapling Growthsupporting
confidence: 83%